Training on Preparation of Accountability Report on the Use of Village Funds for Meunasah Mesjid Punteut Village Apparatus, Blang Mangat District Lhokseumawe City - Marjulin Marjulin; Said Herry Safrizal; Hilmi Hilmi; Teuku Mustaqin; M.Yazid AR (International Journal of Social Service and Research, 2023)
Gampong Meunasah Mesjid Punteut, Blang Mangat sub-district, is a gampong under construction for the service of the Lhokseumawe State Polytechnic, where the gampong has problems in making village fund accountability reports so that training is needed in preparing correct and targeted fund reports, the Gampong Meunasah apparatus of Punteut Mosque is very enthusiastic about participating in the training to compile this Gampong Fund report, so that the results of this service can help the gampong apparatus  aforementioned. The results of this training are expected that the gampong apparatus can understand and also be able to detail and compile accountability reports in accordance with the rules, so as to minimize errors in analyzing estimates that are in accordance with the standard form of village fund reports.